2018
DOI: 10.1016/j.reprotox.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Low dose bisphenol S or ethinyl estradiol exposures during the perinatal period alter female mouse mammary gland development

Abstract: Throughout life, mammary tissue is strongly influenced by hormones. Scientists have hypothesized that synthetic chemicals with hormonal activities could disrupt mammary gland development and contribute to breast diseases and dysfunction. Bisphenol S (BPS) is an estrogenic compound used in many consumer products. In this study, CD-1 mice were exposed to BPS (2 or 200 μg/kg/day) during pregnancy and lactation. Mice exposed to 0.01 or 1 μg/kg/day ethinyl estradiol (EE2), a pharmaceutical estrogen, were also evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 86 publications
(112 reference statements)
0
30
0
Order By: Relevance
“…BPA alters intracellular molecular mechanisms that may cause breast cancer by binding to estrogen-related receptors (ERRs) or G protein-coupled receptors (GPERs). Fetal exposure to low doses of BPA has long-term effects, increasing the risk of breast cancer in adulthood [60].…”
Section: Bisphenol Amentioning
confidence: 99%
“…BPA alters intracellular molecular mechanisms that may cause breast cancer by binding to estrogen-related receptors (ERRs) or G protein-coupled receptors (GPERs). Fetal exposure to low doses of BPA has long-term effects, increasing the risk of breast cancer in adulthood [60].…”
Section: Bisphenol Amentioning
confidence: 99%
“…The low dose (2 μg BPS/kg/day) was selected to approximate human exposures; it is approximately 1–10x higher than typical human intake [3] . The mid dose (200 μg BPS/kg/day) was selected based on prior studies showing that this dose disrupted maternal behaviors, the lactating mother, and development of the mammary gland [2] , [4] , [5] . The highest dose (2000 μg BPS/kg/day) was selected based on results from a recent study at the National Toxicology Program which revealed significant effects of BPS on the female mammary gland at a similar dose (5000 μg/kg/day) [6] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Pregnant mice were exposed from E9.5-E18.5 with 100µg/kg • bodyweight DES, 25µg/kg • bodyweight BPS, or oil control via oral gavage. Doses were chosen to be consistent with previous literature in mouse studies or known human exposures (Hilakivi-Clarke et al 2013;Kolla et al 2018;LaPlante et al 2017;Tucker et al 2018). At 12 weeks of age, mice were subjected to our breast stiffness assay.…”
Section: In Utero Bpa Increases Collagen Matrix Density and Gland Stimentioning
confidence: 99%
“…However, BPS did not show any change in stiffness. Interestingly, BPS induces many of these developmental abnormalities in the mammary gland which are seen with BPA and are typically used as a measure of cancer risk (Kolla et al 2018). While no study has directly tested BPS in a cancer susceptibility model, such as DMBA, its association with these phenotypes has raised concerns.…”
Section: Bpa Alternatives and The Importance Of Estrogenic Activitymentioning
confidence: 99%
See 1 more Smart Citation